Measurement of Solar pp-neutrino flux with Borexino: results and implications. Issue 1 (January 2016) - Smirnov, O Yu; Agostini, M; Appel, S; Bellini, G; Benziger, J; Bick, D; Bonfini, G; Bravo, D; Caccianiga, B; Calaprice, F; Caminata, A; Cavalcante, P; et al.
Abstract: Measurement of the Solar pp-neutrino flux completed the measurement of Solar neutrino fluxes from the pp-chain of reactions in Borexino experiment. The result is in agreement with the prediction of the Standard Solar Model and the MSW/LMA oscillation scenario. A comparison of the total neutrino flux from the Sun with Solar luminosity in photons provides a test of the stability of the Sun on the 10 5 years time scale, and sets a strong limit on the power production by the unknown energy sources in the Sun.